Optimizing the Quantity of Pile Production Using Goal Programming Method - Sukma, Dwi; Arfianto, Alfiyo Ramadhany (AI Society & STMIK Indonesia, 2023)
Goal Programming (GP) is a mathematical model that is used as a basis for making a decision to analyze and make solutions to problems that involve many objectives so that optimal alternative problem solving is obtained. PT Bungah Andya Teknik is a telecommunication network contractor company established on December 24, 2018. PT Bungah Andya Teknik focuses on the production of poles for fiber optic networks. this company only produces 250 pcs of poles every month with a production target that should be 300 pcs of poles every month, with a production cost of IDR 1,500,000 per pcs of poles and with a sales profit of IDR 300,000 per pcs of poles. The revenue obtained by the company in real terms for the period August 2023 to October 2023 is IDR 261,800,000, - and the revenue obtained from the calculation results using the Goal Programming method is IDR 403,900,000, -, so it can be concluded that the Goal Programming method can provide the best solution and the revenue obtained is greater than the company's real income.